Exploring synergy in a mobile learning model for piano playing ornaments exercise with local musical heritage. (August 2022) - Loo, Fung Ying; Chai, Khai Ern; Loo, Fung Chiat; Chua, Yan Piaw
This study addresses the potential of a mobile learning model that integrates local Malaysian musical heritage in piano ornaments finger exercise. An asynchronous model adapted from the concept of karaoke was designed aiming at a synergy of piano exercise, edutainment, and heritage education with visual and auditory accompaniments. We aimed to raise interest and motivation for piano playing ornaments exercise among learners during practice while raising awareness of local musical heritage. A total of 30 piano students aged 13 to 15 years participated in this intervention study; they were equally divided into a control group and an experimental group. The pre- and post-intervention assessments revealed an increase in the levels of motivation, awareness of local musical heritage, and perceived satisfaction factors for the new mobile learning model.